Bahasa & Ijtihad: Aspek Normatifitas Linguistik dalam Kitab Bidayatal-Mujtahid karya Ibnu Rusyd - Abdul Basith (JURNAL PENELITIAN, 2016)
Knowledge of Arabic is an absolute requirement for anyone who wanted to explore the law directly from the Qur'an and hadith. This article aims to reaffirm the importance of the knowledge of the Arabic language by taking a study on the Bidayat al Mujtahid written by Ibn Rushd. The book is not only to show dissent Mujtahid course, but he also explained the cause of such dissent, including that caused by language problems. The article concludes that linguistic terms contained in the book Bidayat al Mujtahid is Nahwu Sciences which includes: letters jarr, 'i'rab, athaf, istitsna', function of hurf al, definition of jama’ and marja' dlamir; Dalalah science and science-related Balaghah especially majaz (removal of the word and figurative meanings) and nature. Differences Mujtahids perspective to the problems this implies a law that they charge.